Analysis of The Availability of HOTS Indicators on Physics Questions for Class X SMA Adabiah 2 Padang During the Covid 19 Pandemic - Apriani Wirahmawati; Dea Sagita; Desnita Desnita (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
In the 2013 curriculum, one of the efforts to improve the quality of human resources in Indonesia is to increase HOTS in the learning of every school student. However, with the COVID-19 pandemic at the beginning of 2019, there have been changes in all areas of life, especially education. Learning during the COVID-19 pandemic was greatly disrupted because of the limited hours of lessons, besides that there were many other obstacles such as the availability of inadequate online learning support media during the COVID-19 pandemic. In addition, the delivery of material delivered by the teacher was also not optimal due to limited circumstances with only through virtual mode. This study aims to determine the availability of HOTS indicators on physics questions at SMA Adabiah 2 Padang during the covid 19 pandemic. This research instrument is an instrument that has been validated with a valid category. The research method used is a documentation study with UTS and UAS assessment sheets for class X MIPA students. Analysis of the data used in determining the availability of HOTS indicators in this Physics problem uses the formula (∑HOTS of components that appear)/(number of HOTS of components that appear) × 100%. In this study, it was found that the percentage value of the availability of the HOTS indicator on UTS questions was lower than on UAS questions, with the percentage of UTS questions being 8% and the percentage on UAS questions being 24%. Then the percentage for problem-solving indicators is 66.7%, decision-making skills indicators are 85.71%, critical thinking skills indicators are 88.89%, and creative thinking skills indicators are 51.14%. Critical thinking ability has the highest percentage value with a value of 88.89%. From the data, it can be concluded that the percentage value of HOTS availability on UTS questions is lower than the UAS percentage value. The value of critical thinking ability has the first highest percentage indicator, then decision-making ability is in the second position, problem-solving skills is in third place, and the last is the ability to think creatively.